The Halal Consumer Dilemma: How Muslim Cognitive Dissonance Bridges Religiosity and Social Media Marketing Toward Visit Intention - Shofura Kamila Hasna; Bethani Suryawardani; Astri Wulandari (International Journal of Social Sciences and Humanities, 2026)
The emergence of modern tourism destinations has generated new considerations for Muslim travelers, particularly when leisure-oriented attractions intersect with religious values. This research explores how religiosity and social media marketing shape visit intention toward Mezzo Beach Club Kebumen, while accounting for the role of Muslim cognitive dissonance. Using a quantitative explanatory design, data were collected from 250 Muslim respondents who had prior knowledge of the destination. The proposed relationships were evaluated through Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS 4. The analysis demonstrates that religiosity contributes to both visit intention and Muslim cognitive dissonance, whereas social media marketing strengthens visit intention without significantly influencing cognitive dissonance. the results further show that higher levels of Muslim cognitive dissonance are associated with lower intention to visit. In addition, Muslim cognitive dissonance serves as a partial explanatory mechanism linking religiosity to visit intention, while no mediating role is identified in the relationship between social media marketing and visit intention. These findings enrich the understanding of Muslim tourist behavior by highlighting the interplay between religious commitment, marketing communication, and psychological evaluation when assessing contemporary tourism destinations.